2006
DOI: 10.1097/00004850-200609000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone monotherapy for post-traumatic stress disorder related to sexual assault and domestic abuse in women

Abstract: Post-traumatic stress disorder is a common, chronic, and often disabling mental illness. Selective serotonin reuptake inhibitors are the usual first-line treatment for post-traumatic stress disorder, but many patients fail to respond adequately. Thus, other treatment options, including the atypical antipsychotics such as risperidone, need to be tested. Women between the ages of 19 and 64 years with post-traumatic stress disorder were enrolled. Symptom severity was rated at baseline using the Treatment Outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…There is also evidence for the efficacy of the antipsychotics risperidone (Padala et al, 2006), olanzapine (Carey et al, 2012) and the anticonvulsant topiramate; (Yeh et al, 2011). Medications which have not been found efficacious in placebo-controlled trials include citalopram, alprazolam, and the anticonvulsants tiagabine and divalproex.…”
Section: Acute Treatment Of Post-traumatic Disordermentioning
confidence: 99%
“…There is also evidence for the efficacy of the antipsychotics risperidone (Padala et al, 2006), olanzapine (Carey et al, 2012) and the anticonvulsant topiramate; (Yeh et al, 2011). Medications which have not been found efficacious in placebo-controlled trials include citalopram, alprazolam, and the anticonvulsants tiagabine and divalproex.…”
Section: Acute Treatment Of Post-traumatic Disordermentioning
confidence: 99%
“…Risperidone was used as a monotherapy in only one study. 6 Only the dimension of avoidance/numbing symptoms did not respond adequately to risperidone in the above mentioned studies. In open trials, most of them involving war veterans with chronic PTSD, risperidone showed to be useful for the decrease of episodes of waking up in the middle of the night and vivid dreams related to the trauma, with evident improvement during the three first weeks of treatment.…”
Section: Methodsmentioning
confidence: 86%
“…Atypical antipsychotics Risperidone was used in the treatment of PTSD in at least five randomized clinical trials. [3][4][5][6][7] In four of them, risperidone had superior results than placebo. In most of the studies, risperidone was added to the therapeutic scheme of the patients who had already been treated with other drugs.…”
Section: Methodsmentioning
confidence: 97%
“…However, post-hoc analyses did reveal an advantage for risperidone in terms of improved sleep. Only a single RCT of risperidone monotherapy in PTSD has been published (Padala et al 2006). In this 12-week study of women (N ¼ 20) with PTSD stemming from sexual assault or domestic abuse, flexibly dosed risperidone (mean dose of 2.62 mg) was well-tolerated and superior to placebo on the primary outcome measure -score on the 8-item Treatment Outcomes PTSD Scale, but not on secondary outcomes (CAPS, HAM-D, or HAM-A).…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%